Ethical and Digital Literacy Challenges in the Utilization of Artificial Intelligence in Pancasila Education: A Systematic Literature Review - Irfanuddin, Muhammad; Karsono, Karsono; Rawanoko, Endrise Septina (Universitas Sebelas Maret, 2026)
The use of artificial intelligence (AI) in education has expanded rapidly, including in Pancasila Education, which is oriented toward the formation of values, character, and citizenship. While AI offers opportunities for innovation in learning planning and instructional design, its application in values-based education also raises serious challenges related to ethics and digital literacy. This study aims to systematically review research findings concerning ethical and digital literacy challenges in the use of AI within Pancasila Education. The method employed is a Systematic Literature Review (SLR) following the PRISMA guidelines. Relevant articles were collected from national and international databases through a selection process based on predefined inclusion and exclusion criteria and were analyzed using a thematic synthesis approach. The findings indicate that the main challenges include teachers’ dependence on AI, potential algorithmic bias in the representation of values, weak content verification, and the risk of dehumanizing value-based learning. In addition, the literature reveals that teachers’ levels of digital literacy significantly influence the quality and responsibility of AI use in educational practices. Limited understanding of digital ethics tends to encourage pragmatic uses of AI that overlook reflective processes essential for the internalization of Pancasila values. This study concludes that the integration of ethical considerations and the strengthening of digital literacy are essential prerequisites for the responsible use of AI in Pancasila Education. These findings are expected to provide a conceptual foundation for policy development, teacher competency enhancement, and the use of AI that aligns with Pancasila values and the principles of humanistic education